Improvement Efforts Creativity through Activity Sand Painting for Children Aged 5 – 6 Years - Susila, Susila; Suryani, Yuni Dwi (Universitas Pahlawan Tuanku Tambusai, 2025)
This classroom action research (CAR) aims to improve children's creativity through sand painting activities. The background of this study is the low level of creativity observed among children in group B3 at Az-Zahrah Islamic Kindergarten, Palembang. Many children still face difficulties in developing ideas, imagination, and creativity. They tend to imitate given examples, showing limited flexibility, originality, and innovation, and often appear hesitant to try new approaches. Furthermore, some children lack interest in coloring activities. Based on pre-cycle observations, out of 15 children, 13 (87%) were categorized as “Starting to Develop” (MB), while only 2 children (13%) reached the “Developing as Expected” (BSH) category. The research was conducted over two cycles, with each cycle consisting of six meetings. The participants were selected using purposive sampling, focusing on group B3 students. Data were collected through observations, checklists, and field notes. The results of the study show that in Cycle I, 11 children (73%) achieved the BSH category. In Cycle II, the number increased to 12 children (80%) in the BSH category, and 4 children (20%) reached the “Very Well Developed” (BSB) category. These findings indicate that sand painting activities are effective in enhancing children's creativity. Therefore, it is recommended that teachers incorporate sand painting into their learning activities to foster creativity among young learners.